Wendell Minor art for the written word : twenty-five years of book cover art - Minor, Wendell (Harcourt Brace & Company, 1995)
This one-of-a-kind retrospective brings together a rich selection of pieces from Wendell Minor's extraordinary body of jacket art, coupled with lively commentary from authors and others in publishing on the relationship between a book's cover and what is inside. The volume includes over one hundred full-color reproductions of artwork from the jackets of best-selling books by Ray Bradbury, Mary Higgins Clark, Pat Conroy, Louise Erdrich, John Hersey, Patricia Maclachlan, Larry McMurtry, James A. Michener, Toni Morrison, Judith Rossner, Martin Cruz Smith, Elizabeth Marshall Thomas, Paul Theroux, and many, many more.